Cortisol and α-amylase awakening response in children and adolescents with functional neurological (conversion) disorder. (January 2023) - Chung, Jason; Mukerji, Shohini; Kozlowska, Kasia
Objective: Stress system dysregulation is considered to have an important role in the aetiology of paediatric functional neurological (conversion) disorder. This study examined salivary cortisol and α-amylase awakening responses in children with functional neurological disorder to determine activation patterns of the hypothalamic–pituitary–adrenal axis and sympathetic system. A healthy cortisol awakening response involves a robust increase in cortisol within 30 minutes of awakening. Alpha-amylase awakening response is variable in children. Methods: Cortisol and α-amylase were measured in saliva from 32 patients with functional neurological disorder (26 girls and 6 boys, aged 11.3−16.1 years) and 31 healthy controls (23 girls and 8 boys, aged 8.6–17.7 years). Saliva samples were collected using a Salivette sampling device at two time points – upon awakening and 30 minutes after awakening. Results: Patients with functional neurological disorder showed a decrease in cortisol awakening response (–4 nmol.min/L) and controls showed an increase (107 nmol.min/L), t (55) = –.4.6, p < 0.001. Within the functional neurological disorder group, 57% showed an attenuated cortisol awakening response and 43% showed an obliterated/reversed cortisol awakening response: Cortisol awakening response was negatively correlated with adverse childhood experiences, r (58) = –0.6, p = 0.002, and subjective distress (total Depression Anxiety and Stress Scales score), r (58) = –0.4, p = 0.050. In controls, cortisol awakening response showed no correlation with adverse childhood experiences and a positive correlation with subjective distress, r (56) = 0.4, p = 0.023. Total cortisol remained similar between the functional neurological disorder and control group. No significant differences were observed between the functional neurological disorder and control group in any of the α-amylase analyses. Discussion: The results suggest dysregulation of the hypothalamic–pituitary–adrenal axis in children with functional neurological disorder. Hypothalamic–pituitary–adrenal dysregulation in children with functional neurological disorder may contribute to comorbid symptoms of fatigue, sleep disturbance and subjective loss of well-being because circadian rhythms and energy metabolism are disrupted. Hypothalamic–pituitary–adrenal dysregulation – and changes in glucocorticoid (cortisol) signalling at the molecular level – may also contribute to increased vulnerability for functional neurological disorder symptoms because of epigenetically mediated changes to neural networks implicated in functional neurological disorder.